PENERAPAN MANAJEMEN KURIKULUM DALAM MENINGKATKAN KETERAMPILAN SOSIAL (Social Skill) DI MAN DARUSSALAM CIAMIS - Ibrahim, Tatang (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2017)
AbstractThis study aims to determine the curriculum planner in improving social skills (social skills), the implementation of curriculum in improving social skills (social skill), the form of curriculum evaluation so far in improving social skills (especially skill) in the skills lessons held in MAN Darussalam Ciamis.This study is a qualitative descriptive analytic study of data collection is done by data collection techniques documentation, observation, and in-depth interviews (In depth interview). To analyze the data, this study uses inductive data analysis with an inductive approach opening the possibility to perform discovery or discovery.The results of this study show that: (1) Planning of curriculum in improving social skill (social skill) in MAN Darussalam Ciamis implemented by way of compilation of vision, mission, and purpose of education, education calendar, curriculum structure. (2) The implementation of curriculum in improving social skills in MAN Darussalam Ciamis covers the implementation of programmed activities consisting of: religious, social, bilingual program. (3) The form of evaluation of curriculum in improving social skill (social skill) in MAN Darussalam Ciamis, is carried out with two stages: writing test and individual practice test. With held the examinations were able to improve the social skills of learners because in addition to getting the material also directly practice with the tools of existing skills.